Athletic identity, sport participation, and psychological adjustment in people with spinal cord injury - Tasiemski, T.; Brewer, B. W. (Adapted Physical Activity Quarterly, 2011)
This study examined interrelationships among athletic identity, sport participation, and psychological adjustment in a sample of people with spinal cord injury (SCI). Participants (N = 1,034) completed measures of athletic identity, life satisfaction, anxiety, depression, and demographic and sport participation variables. Current amount of weekly sport participation was positively related to athletic identity when statistically controlling for age, gender, and pre-SCI amount of weekly sport participation. Being able to practice one`s favorite sport after SCI was associated with higher levels of athletic identity and better psychological adjustment. Team sport participants reported experiencing better psychological adjustment than individual sport participants did. The findings suggest that social factors are important in the link between sport participation and psychological adjustment in people with SCI.